The way we wed : a global history of wedding fashion - Chrisman-Campbell, Kimberly (Running Press, 2020)
"The Way We Wed is an expansive history from the Renaissance to the present day, chronicling the evolution of nuptial style. It's a mix of A-list and historical wedding couples, same-sex marriages, royal weddings, wartime brides, White House weddings, and cross-cultural celebrations. The fashions include gowns from around the globe as well as going-away dresses, accessories, and clothes worn by flower girls, bridesmaids, guests, and grooms" -- Back cover.